(untitled) (Педагогіка вищої та середньої школи, 2022)
Various theoretical approaches to the definition of insight and the contents of the terms “active communicative position ” in scientific research are considered in the article. The author substantiated the necessity o f the form ation o f the pupils’ active communicative position in the process o f studying.